Immunohistochemical and bioinformatics analysis of the placental BCL-2 and Beclin-1 expressions in preeclampsia and HELLP syndrome - Süleyman Cemil Oğlak; Fırat Aşır; Emine Zeynep Yılmaz; Ayşegül Aşır; Gökhan Bolluk; Tuğcan Korak; Hayat Ayaz; Elif Ağaçayak (Journal of Obstetrics and Gynaecology)
Background This study aimed to examine the alterations in apoptosis and autophagy in placental tissues from normal pregnancies compared to those affected by preeclampsia (PE) and HELLP (haemolysis, elevated liver enzymes, low platelets) syndrome. We analysed the expression of autophagy-associated proteins, Beclin-1 and BCL-2, in human placental tissues and assessed their variations in placentas from pregnancies complicated by PE and HELLP syndrome by immunohistochemical (IHC) and in silico analyses.Methods An experimental case-control study was performed, involving 40 pregnant women complicated with preeclampsia, 25 pregnant women with HELLP syndrome, and 40 healthy pregnant women. The placental sections were stained with BCL-2 and Beclin-1 immunostains and subjected to IHC examination. The results of the IHC staining were assessed using semi-quantitative analysis. In silico analyses were performed using STRING and Cytoscape software to construct protein interaction networks for BCL-2 and Beclin-1 in PE and HELLP syndrome, followed by Gene Ontology analysis of common interactors to identify significant biological pathways.Results Both BCL-2 expression was significantly decreased (p < 0.001 and p < 0.0001, respectively) and Beclin-1 staining was significantly increased (p < 0.0001 and p < 0.0001, respectively) in the PE group and HELLP group compared to the control group. The changes in BCL-2 and Beclin-1 expression between PE and the HELLP group were also statistically significant. BCL2 expression was notably lower (p < 0.0001), and Beclin-1 staining was significantly higher (p < 0.05) in the HELLP group compared to the PE group. In PE, BCL-2 interactors were enriched in apoptosis, cytokine production, and cell proliferation pathways, while Beclin-1 interactors were linked to autophagy and phosphatidylinositol-mediated signalling. In HELLP, BCL-2 interactors were involved in inflammatory response regulation, whereas Beclin-1 interactors were associated with vascular endothelial growth factor (VEGF) signalling and immune regulation.Conclusions The differential expression patterns of BCL-2 and Beclin-1 between the PE and HELLP groups suggest that these proteins play distinct roles in the pathophysiology of these conditions.